Knowledge about Labor Influence on Primigravide Readiness for Labor - Erma Nur Fauziandari (Universitas STRADA Indonesia, 2023)
Background: The high maternal mortality rate in Indonesia is caused by the unpreparedness of mothers in facing childbirth. Many things affect the readiness of mothers in facing childbirth. The factors that affect the readiness of the mother are knowledge, education, socio-culture and economy. Purpose: Knowledge influences primigravida readiness to face childbirth. Methods: This type of research is analytical research with an observational approach. Sampling was taken by purposive sampling with the criteria primigravida with a minimum gestational age of 28 weeks. Data analysis used chi square statistical analysis. Results: The sample in this study was 53 primigravidas with the third trimester of gestation. The results of statistical tests show that the p value is 0.00 <0.05. These results suggest that the hypothesis is accepted, namely that knowledge affects primigravida readiness for labor. Conclusion: The better the primigravida knowledge, the better prepared it will be to face childbirth.